Efficacy of focused group discussion on knowledge and practices related to menstruation among adolescent girls of rural areas of rhtc of a medical college: An interventional study - Prashant Ramdas Kokiwar; P Nikitha (Wolters Kluwer Medknow Publications, 2020)
Context: Learning about menstrual hygiene is vital part of health education for adolescent girls so that they can continue to work and maintain hygienic habits throughout their adult life. Aim: The aim is to study the efficacy of focused group discussion (FGD) in comparison to didactic lecture method (DL) on knowledge and practices related to menstruation among adolescent girls of rural areas. Materials and Methods: Community-based interventional study was carried out among 260 adolescent girls. Knowledge and practice were assessed with the help of questionnaire preintervention. During intervention, 130 girls in DL group were given DL and 130 girls in FGD received FGD. After 2 months, all 260 girls were contacted. Their knowledge and practices were assessed using same questionnaire. Statistical Analysis: Yates corrected Chi-square and Student's t-test was used. Results: Both methods were equally effective in increasing mean knowledge and practices score (P < 0.05). On comparison of mean postintervention scores between the two groups for knowledge, the FGD method was found to be superior (P < 0.05) but not for practices (P > 0.05). Conclusion: FGD was more effective than DL method for knowledge related to menstruation but not for practices.